Ordinal regression of rice technology adoption in Pinrang, Indonesia - HASNAL HASNAL; MUH. FARID BDR; AKHSAN AKHSAN; MUHAMMAD HATTA JAMIL; SYAHDAR BABA (Smujo International, 2026)
Abstract. Hasnal, BDR MF, Akhsan, Jamil MH, Baba S. 2026. Ordinal regression of rice technology adoption in Pinrang, Indonesia. Asian J Agric 10 (1): g100146. https://doi.org/10.13057/asianjagric/g100146. The agricultural sector continues to play a vital role in sustaining livelihoods in Indonesia, contributing significantly to national food security and rural economic development, with rice as the staple food. However, the decline in rice cultivation area and productivity in Pinrang District highlights the need to enhance the adoption of agricultural technology. Optimizing rice production requires intensive management, including the use of modern equipment, high-yielding varieties, and the implementation of sustainable agricultural practices. This study examines the socioeconomic factors influencing the adoption of rice farming technology amid increasing agricultural digitalisation. The results indicate that most farmers are at a moderate level of technology adoption, suggesting uneven diffusion across farmer groups. Formal education, distance from home to farmland, extension intensity, and household income emerged as key positive predictors of adoption. In contrast, participation in non-formal education had a negative effect, particularly among farmers who had never attended non-formal training. These findings provide important insights for policymakers and stakeholders in designing targeted interventions, strengthening extension services, and improving access to education and resources to promote wider adoption of agricultural technologies and ultimately enhance rice productivity and farmers’ welfare.